Analisis Skala Ekonomis Industri Kebaya Bordir Di Kota Denpasar - Yanto, Norman Budi; Djayastra, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
The development of the industrial sector will be strongly influenced by the scale of business or production scale and efficient use of production factors. The industrial sector in the city of Denpasar has been growing rapidly. One is the kebaya embroidery industry. This study aims to determine the economic scale on the kebaya embroidery industry in Denpasar. Th . is rese . arch w . as cond . ucted i . n t . he ci . ty o . f Den . pasar by all employers respondents kebaya embroidery industry in the city of Denpasar as much as 34 employers. T . he ana . lysis tech . nique us . ed i . s mul . tiple lin . ear regr . ession model transf . ormation Cobb-Douglas. The results showed, the economic scale of kebaya embroidery industry in Denpasar in a state of Increasing Return to Scale. Namely the increasing scale indicated by the rate of production is greater than the rate of increase in the average cost. The nature of industrial production kebaya embroidery in Denpasar labor intensive indicated by the lab . or coef . ficient gre . ater th . an th . e coeff . icient o . f cap . ital.
Keywords: embroidered kebaya industrial production; labor; capital